PENGARUH PELATIHAN DAN MOTIVASI TERHADAP PRODUKTIVITAS KERJA PEGAWAI PADA KEMENTERIAN PARIWISATA - Agustina Massora (Fakultas Ekonomi Universitas Borobudur, 2018)
This study aims to determine the extent of the relationship of training, motivation to work productivity of employees at the Ministry of Tourism, and to find out how the influence of training factors, motivation on work productivity. In this study the authors distributed questionnaires to 38 respondents with a Simple Random Sampling technique and with the data analysis method used were multiple regression and F test multiple correlation.Based on the calculation, regression is obtained Y = 2,386 + 0,858 X1 + 0,165 X2 which means that every increase in training variable (X1) will be followed by an increase in work productivity, every increase in the motivation variable will be followed by an increase in work productivity. With the existence of R = 0.91, this indicates that there is a level of strong and positive relationship between training and motivation with work productivity. This means that the increase in training and motivation drives the increase in work productivity. From testing with hypothesis F it is known that F count is 83.806 while F table is 3.27 with dk numerator 2 (= k-1 = 3-1) and d denominator n - k = 38 - 3 = 35. Because F count is greater than F table, Ho is rejected and Ha is accepted, meaning that there is a relationship between training (X1) and motivation (X2) on work productivity (Y).From the determination coefficient of 82.7%, this shows that the effect of training and motivation is 82.7% on the increase in work productivity, while the remaining 17.3% is influenced by other variables not included in this research model. For further research, it is expected to add other variables related to work productivity such as organizational commitment, compensation, leadership and others, thus it can be better known the influence of other factors that will affect work productivity.Keywords: Training, Motivation, Work Productivity.